Formação de professores, lógica de programação e matemática: uma somatória possível? - Pauli, Ines Cristina de Castilhos [UNIFESP] (2020)
This research was carried out in a Municipal Basic Education School in São Bernardo do Campo, SP, with the objective of observing the technological training of regular teachers of the fourth and fifth years and if the work developed by Teacher of Support to Pedagogical Projects related to Technology (PAPPTEC), when using programming logic through the Scratch program, was able to promote a training action with the aforementioned teachers, and if they had the perception that they could apply the tool in the construction of knowledge of students in a contextualized way, with respect to mathematical objects. The case study methodology was adopted and the surveys were carried out by means of questionnaires, interviews, observation in the laboratory and analysis of the Political Pedagogical Project of the school unit in confrontation with the municipality's curriculum proposal regarding the application of technology in the process of teaching and learning. This study concludes that the utilized tool was exclusively based on PAPPTEC planning and as an exploration of the material in detriment to a specific content; regular teachers were unable to relate and systematize its use as a possible and convergent proposal with the learning of mathematical objects that were being taught during classes. The teachers considered that the logic of programming could be used as a strategy, but not as a methodological approach or pertinent to the teaching and learning necessary for the development of the skills proposed for the year. Teachers did not consider that PAPPTEC also aimed at training them while developing projects with students. This study notes that it will be necessary to approach and plan between the PAPPTECs and the regular teachers, regarding the skills to be developed for each year, more aligned to the learning objects. The school is a space that produces knowledge, in addition to teaching it and where learning takes place effectively. During the process of construction of teaching knowledge, teachers become qualified to choose the most suitable methodology to achieve the learning of the proposed knowledge objects, enabling the related skills to be developed in the students. The responses obtained in the questionnaire demonstrate that all teachers have sought continuing education in recent years. The study also reveals that we should review the use of technological equipment for students in the early years of basic education because the effect may be contrary to what is desired, especially regarding the development of creative thinking.